Laws of the Commonwealth of Pennsylvania, from the Fourteenth Day of October, One Thousand Seven Hundred, to the Twentieth Day of March, One Thousand Eight Hundred and Ten, at 182, ch. 1746, § 10 (Vol. 3, 1810) - (:unkn) unknown (My University, 1810)
§That if any person within this commonwealth shall challenge, by word or writing, the person of another to fight at sword, rapier, pistol, or other deadly weapon, such person so challenging, shall forfeit and pay for every such offense
Keywords: DUELING